2004
DOI: 10.1587/elex.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Induced Fluorine Damage in P-HEMT Caused by C2F6/CHF3 RIE Plasma

Abstract: Fluorine atoms intruded into the channel layer in P-HEMT and degraded its carrier density and electron mobility during the SiO 2 RIE process. Thermal annealing at 300 • C for 10 minutes was rather effective for recovering from this plasma damage. Our SIMS investigation revealed that the mechanism of this recovery was the removal of fluorine atoms from the channel layer and their accumulation in the δ-doped Si layer. Ionized impurities in the channel layer were removed, and electron mobility was significantly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2004
2004
2006
2006

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
3
1
Order By: Relevance
“…The carrier density decreased to 0.65 after RIE and recovered to 0.85 after thermal annealing, while the electron mobility decreased to 0.80 and recovered to 0.97. Compared with those of the conventional P-HEMT we previously measured [1], the carrier density and electron mobility improved by 0.43 and 0.35 after RIE and by 0.36 and 0.11 after thermal annealing. We considered the strained InSb barrier resulted in fluorine trapping and created the remarkable improvement, as we expected.…”
Section: Methodscontrasting
confidence: 55%
See 2 more Smart Citations
“…The carrier density decreased to 0.65 after RIE and recovered to 0.85 after thermal annealing, while the electron mobility decreased to 0.80 and recovered to 0.97. Compared with those of the conventional P-HEMT we previously measured [1], the carrier density and electron mobility improved by 0.43 and 0.35 after RIE and by 0.36 and 0.11 after thermal annealing. We considered the strained InSb barrier resulted in fluorine trapping and created the remarkable improvement, as we expected.…”
Section: Methodscontrasting
confidence: 55%
“…The P-HEMT structure was composed of, an undoped GaAs buffer layer, an undoped Al 0.3 Ga 0.7 As buffer layer (50 nm), an undoped GaAs buffer layer (50 nm), an In 0.25 Ga 0.75 As channel layer (8 nm), a Si-doped Al 0.3 Ga 0.7 As layer (5 nm), a δ-doped Si layer (5.0 × 10 12 cm −2 ), an undoped Al 0.3 Ga 0.7 As Schottky layer (20 nm), an undoped InSb fluorine barrier (0.6 nm), an undoped Al 0.3 Ga 0.7 As layer (3 nm), and an undoped GaAs cap layer (10 nm), as listed in Table I. We inserted a strained InSb layer as a fluorine barrier into the Al 0.3 Ga 0.7 As Schottky layer of the conventional P-HEMT structure we had previously used [1]. The sample was exposed to C 2 F 6 /CHF 3 RIE plasma generated by a Lam Research TE-580 dry etching system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that fluorine-based reactive ion etching (RIE) plasma seriously affects the active layers in pseudomorphic-high electron mobility transistors (P-HEMTs) because of fluorine impurities originating from the plasma [1]. We also reported that fluorine accumulates in strained interfaces, like a hetero interface or a δ-doped layer.…”
Section: Introductionmentioning
confidence: 99%